(untitled) (Bangladesh Journal of Medical Science, 2025)
Aim is to develop a program for injury prevention using rehabilitation measures and targeted strengthening of the musculoskeletal system in Greco-Roman wrestlers. Methods The study involved 186 athletes of various qualifications who were engaged in Greco-Roman wrestling at a school of high sports mastery. Two groups of 26 people were formed, they took part in the pedagogical experiment during 12 academic months. All athletes trained according to the standard program for training wrestlers. In the experimental group, an additional experimental program for injury prevention was used, which included educational work with wrestlers, massage and self-massage, use of a sauna, proper warmup, special muscle training, strengthening of the musculoskeletal system, fatigue prevention, and keeping a diary of athlete selfmonitoring. Results The comparative analysis of the indicators for the period of the pedagogical experiment showed that in the experimental group the number of minor injuries decreased from 85 to 66 (22.4%), the number of moderate injuries decreases from 173 to 156 (9.8%), and the number of severe injuries decreased from 45 to 38 (15.6%). In the control group, the number of minor injuries decreased from 78 to 73, the number of moderate injuries decreased from 159 to 151 (5%), and the number of severe injuries increased from 60 to 62 (3.2%). At the end of the pedagogical experiment, the injury rate in the experimental group decreased by a total of 14.2% (P < 0.05), and in the control group by 3.7% (P > 0.05). Conclusion Based on the results of the pedagogical experiment, it can be concluded that, to a certain extent, sports injuries are a manageable process. And if organization of preventive measures is appropriate, sports injuries can be reduced to minimum, especially the number of moderate and severe injuries. Thus, the injury prevention program for Greco-Roman wrestling has proven its effectiveness in the course of the practical pedagogical experiment and can be used in children’s and professional wrestling schools. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 423-432